The catholic religious assistance in the Armed Forces of Argentina, Brazil and Chile - Precht Pizarro, Jorge (Derecho Público Iberoamericano, 2013)
This article provides a summary of the catholic religious assistance legal regime for the armed forces in Argentina, Brazil and Chile. It addresses the current problems for the state ecclesiastical legal order and for canonical law.